L'informazione allo "stato naturale" - Giovanni Caturano (Archeomatica, 2023)
By examining the evolution of visual communication from ancient cave paintings to modern virtual reality, this article highlights the potential of virtual technologies in creating three-dimensional and spatialized information that is more accessible to our brains and bodies. The text discusses various examples of immersive experiences, from virtual exhibitions to innovative applications in archaeology and the arts. Additionally, it emphasizes the importance of multidisciplinary approaches and the connection between technology and beauty, concluding that a demystified vision of the metaverse can complement reality by offering unique experiences and powerful tools for collaboration and interaction.